The importance of skin-to-skin contact and the participation of the nurse in the execution of the procedure - Purificação, Michely Machado da (Seven Editora, 2024)
Early skin-to-skin contact (PPC) corresponds to placing the naked baby on the naked mother’s lap or chest, soon after birth. This practice brings immunological, hormonal and physiological benefits for both, in addition to favoring breastfeeding. Nursing is an area responsible for providing humanized care in the delivery room. Thus, this article aims to: Address the role of nurses in the practice of CPP in obstetric centers. The article is a bibliographic review, with a descriptive character and a qualitative approach. Thus, from the literature, the importance of CPP for the approximation between mother and child was proven, positively reflecting on their survival, in addition to placing the nurse as a facilitator of this communication and a determining professional for the practice. DOI:https://doi.org/10.56238/sevened2024.001-025